Gray Matter Alterations in Parkinson's Disease With Rapid Eye Movement Sleep Behavior Disorder: A Meta-Analysis of Voxel-Based Morphometry Studies - Yang, Chengxian; Chang, Jianbo; Liang, Xiaohang; Bao, Xinjie; Wang, Renzhi (Frontiers in Aging Neuroscience, 2020)
Background: Grey matter (GM) alterations in Parkinson’s disease (PD) patients with rapid eye movement sleep behavior disorder (RBD) have been demonstrated in many neuroimaging studies using voxel-based morphometry (VBM). However, the inconsistent findings between studies cannot be applied to clinical practice as a neuroimaging biomarker. We performed a meta-analysis of VBM studies at a whole-brain level to investigate GM differences between PD patients with and without RBD. Methods: A systematic search was conducted in PubMed, Embase, and Web of Science from inception to November 2019 to identify eligible VBM studies. We adopted the latest Seed-based d Mapping with Permutation of Subject Images technique to quantitatively estimate the difference of regional GM volume between PD patients with and without RBD. Results: We included five studies comprising 105 PD patients with RBD and 140 PD patients without RBD. The pooled meta-analysis revealed that PD patients with RBD showed a significant reduction of GM volume in the right superior temporal gyrus (STG) compared with those without RBD. This result was confirmed to be robust by the jackknife sensitivity analysis. Conclusion: Our finding shows significantly and robustly reduced GM volume in the right STG in PD patients with RBD, preliminarily suggesting the association of GM atrophy in this brain region with the occurrence of RBD in PD patients.